Adhesive layer, circuit substrate using the same, and stripline

CN115141560BActive Publication Date: 2026-10-30NIPPON STEEL CHEM & MATERIAL CO LTD
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
CN202210299416.2
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Priority Date
2021-03-31
Filing Date
2022-03-25
Publication Date
2026-10-30
Estimated Expiration
2042-03-25

AI Technical Summary

Technical Problem

但是,在粘合片中使用柔软、玻璃化转变温度低、热膨胀系数大的树脂材料,因此若增大其厚度,则担心尺寸稳定性降低,进而存在因通过激光加工形成通孔(贯通孔)等的工序而在粘接性树脂层中产生切削、凹沟等损伤,或者在焊接工序等中因热而发生树脂的流出等问题

Benefits of technology

[0043]本发明的粘合层由于实现了低介电损耗角正切化与尺寸稳定性的并存,因此在应用于传输GHz频带(例如,1GHz~50GHz)的高频信号的带状线等电路基板的情况下,可有效地减少高频信号的传输损耗,并且可通过优异的尺寸稳定性来实现可靠性与良率的提高。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN115141560B_ABST
    Figure CN115141560B_ABST
Patent Text Reader

Abstract

Provided is an adhesive layer in which low dielectric loss tangent and dimensional stability coexist, a circuit board using the same, and a strip line. An adhesive layer includes a first adhesive layer, a polyimide layer, and a second adhesive layer, and satisfies: a) the thickness of the entire adhesive layer is in a range of 50 μm or more and 300 μm or less, and the ratio of the thickness of the polyimide layer to the thickness of the entire adhesive layer is in a range of 0.2 or more and 0.9 or less; b) the moisture absorption rate, which is measured after drying for 1 hour at 80°C, followed by conditioning for 24 hours at 23°C, 50% RH, is 0.4% by weight or less; and c) the storage elastic modulus of the first adhesive layer and the second adhesive layer at 50°C is independently 1800 MPa or less, and the maximum value of the storage elastic modulus at 180°C to 260°C is independently 800 MPa or less.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to an adhesive layer that can be effectively used as a material for electronic components, a circuit board using the adhesive layer, and a stripline. Background Technology

[0002] In recent years, with the advancements in miniaturization, weight reduction, and space-saving of electronic devices, the demand for thin, lightweight, flexible, and highly durable flexible printed circuits (FPCs) that withstand repeated bending has increased. FPCs can achieve three-dimensional and high-density installation even in limited spaces; therefore, their applications are gradually expanding in wiring, cables, connectors, and other components of movable parts in electronic devices such as hard disk drives (HDDs), digital video discs (DVDs), and smartphones.

[0003] In addition to increasing density, the performance of devices is also being promoted, which necessitates addressing the increasing frequency of transmitted signals. When transmitting high-frequency signals, significant transmission losses along the transmission path can lead to signal loss or longer signal delays. Therefore, the use of polyimide with a low dielectric loss tangent as the material for multiple resin layers in FPCs has been proposed (e.g., Patent Document 1, Patent Document 2).

[0004] To cope with fifth-generation (5G) mobile communication systems, there is a strong demand for suppressing transmission losses in the GHz band, particularly for striplines, a form of FPC used as transmission paths for radio frequency (RF) cables. Effective methods to suppress stripline transmission losses include: i) achieving a low dielectric loss tangent in the resin material; and ii) increasing the overall thickness of the resin layer. Regarding ii), increasing the thickness of the layer (adhesive resin layer) formed by the adhesive sheet embedded in the stripline is an effective approach. However, the adhesive sheet uses a soft resin material with a low glass transition temperature and a high coefficient of thermal expansion. Therefore, increasing its thickness raises concerns about reduced dimensional stability, potential damage such as cutting and grooves in the adhesive resin layer caused by processes like laser-cutting through-holes, and resin leakage due to heat during welding processes. Therefore, there are limits to increasing the thickness of the adhesive sheet.

[0005] [Existing technical documents]

[0006] [Patent Literature]

[0007] [Patent Document 1] Japanese Patent Application Publication No. 2018-170417

[0008] [Patent Document 2] Japanese Patent Application Publication No. 2020-55186 Summary of the Invention

[0009] [The problem the invention aims to solve]

[0010] As a means to overcome the aforementioned shortcomings of adhesive sheets, bonding plies are used, in which a resin layer with high heat resistance is sandwiched between adhesive resin layers. However, regarding the resin materials used in the bonding ply, there has been almost no research to date on achieving both low dielectric loss tangent and dimensional stability.

[0011] The purpose of this invention is: first, to provide an adhesive layer that can achieve both low dielectric loss tangent and dimensional stability; second, to provide a stripline and other circuit substrates with low transmission loss of high-frequency signals, excellent dimensional stability, and high reliability by using the adhesive layer.

[0012] [Technical means to solve the problem]

[0013] Through diligent research, the inventors discovered that by using a resin with a low storage elastic modulus as the adhesive resin layer in an adhesive layer structure formed by sandwiching a polyimide layer between adhesive resin layers, and by taking into account the thickness ratio of each layer and the overall moisture absorption rate, the aforementioned problems can be solved, thus completing the present invention.

[0014] That is, the adhesive layer of the present invention is an adhesive layer comprising the following layers:

[0015] Polyimide layer;

[0016] A first adhesive layer is laminated on one side of the polyimide layer; and

[0017] The second adhesive layer is laminated on the side of the polyimide layer opposite to the first adhesive layer.

[0018] Furthermore, the adhesive layer of the present invention is characterized by satisfying the following conditions a to c:

[0019] a) The overall thickness of the adhesive layer is in the range of 50 μm or more and 300 μm or less, and the ratio of the thickness of the polyimide layer to the overall thickness of the adhesive layer is in the range of 0.2 or more and 0.9 or less.

[0020] b) The moisture absorption rate was less than 0.4% by weight after drying at 80°C for 1 hour and conditioning at 23°C and 50%RH for 24 hours.

[0021] c) The storage elastic modulus of the first adhesive layer and the second adhesive layer at 50°C is independently below 1800 MPa, and the maximum value of the storage elastic modulus at 180°C to 260°C is independently below 800 MPa.

[0022] The adhesive layer of the present invention may also satisfy the following condition d:

[0023] d) After conditioning for 24 hours under constant temperature and humidity conditions (normal) of 23℃ and 50%RH, the dielectric loss tangent at 10GHz, measured using a split post dielectric resonator (SPDR), was below 0.004.

[0024] In the adhesive layer of the present invention, the glass transition temperature (Tg) of the first adhesive layer and the second adhesive layer can be below 180°C.

[0025] In the adhesive layer of the present invention, the first adhesive layer and the second adhesive layer contain polyimide as a resin component.

[0026] The polyimide may contain anhydride residues derived from the tetracarboxylic anhydride component and diamine residues derived from the diamine component, and may contain more than 50 mol% of diamine residues derived from the dimer diamine composition, wherein the dimer diamine composition is a dimer diamine whose two terminal carboxylic acid groups are replaced with primary aminomethyl or amino groups as the main component.

[0027] In the adhesive layer of the present invention, the coefficient of thermal expansion of the polyimide layer can be in the range of 1 ppm / K or higher and 30 ppm / K or lower.

[0028] In the adhesive layer of the present invention, the dielectric loss tangent of the polyimide layer at 10 GHz, measured by a split column dielectric resonator (SPDR), can be below 0.006 after 24 hours of conditioning under constant temperature and humidity conditions (normal) of 23°C and 50%RH.

[0029] In the adhesive layer of the present invention, the polyimide constituting the polyimide layer may contain tetracarboxylic acid residues and diamine residues, and the content of diamine residues derived from the diamine compound represented by the following general formula (A1) may be 50 mol% or more relative to all diamine residues.

[0030] [Chemistry 1]

[0031]

[0032] [In formula (A1), the linker Z represents a single bond or -COO-, Y independently represents a monovalent hydrocarbon with 1 to 3 carbon atoms that can be substituted with a halogen atom or a phenyl group, or an alkoxy group with 1 to 3 carbon atoms, or a perfluoroalkyl group or alkenyl group with 1 to 3 carbon atoms, n represents an integer from 0 to 2, and p and q independently represent integers from 0 to 4.]

[0033] The circuit board of the present invention includes any of the above-described adhesive layers.

[0034] The strip of the present invention includes:

[0035] First metal layer;

[0036] The first insulating resin layer comprises one or more layers stacked on one side of the first metal layer;

[0037] The wiring layer is grounded to the first insulating resin layer;

[0038] Second metal layer;

[0039] The second insulating resin layer comprises one or more layers laminated on one side of the second metal layer; and

[0040] An intermediate resin layer exists between the first insulating resin layer and the second insulating resin layer in a stacked configuration.

[0041] The intermediate resin layer includes any of the aforementioned adhesive layers, and the wiring layer is covered by either the first adhesive layer or the second adhesive layer.

[0042] [The effects of the invention]

[0043] The adhesive layer of the present invention achieves both low dielectric loss tangent and dimensional stability. Therefore, when applied to circuit substrates such as striplines that transmit high-frequency signals in the GHz band (e.g., 1 GHz to 50 GHz), it can effectively reduce the transmission loss of high-frequency signals and improve reliability and yield through excellent dimensional stability. Attached Figure Description

[0044] Figure 1 This is a schematic diagram showing the cross-sectional structure of the adhesive layer according to an embodiment of the present invention.

[0045] Figure 2 This is a schematic cross-sectional view showing the structure of the strip line according to a preferred embodiment of the present invention.

[0046] [Explanation of Symbols]

[0047] 10: Polyimide layer

[0048] 20A: First adhesive layer

[0049] 20B: Second adhesive layer

[0050] 30A: First metal layer

[0051] 30B: Second metal layer

[0052] 40A: First insulating resin layer

[0053] 40B: Second insulating resin layer

[0054] 50: Wiring layer

[0055] 60A: First layer of stack

[0056] 60B: Second layer

[0057] 100: Adhesive layer

[0058] 101: Intermediate resin layer

[0059] 200: Strip line

[0060] T1, T2: Thickness Detailed Implementation

[0061] The embodiments of the present invention will be described with reference to the accompanying drawings.

[0062] [Adhesive layer]

[0063] Figure 1 This is a schematic diagram showing a cross-sectional structure of the adhesive layer according to an embodiment of the present invention. The adhesive layer 100 of this embodiment includes a polyimide layer 10, a first adhesive layer 20A laminated on one side of the polyimide layer 10, and a second adhesive layer 20B laminated on the side of the polyimide layer 10 opposite to the first adhesive layer 20A. That is, the adhesive layer 100 has a structure in which the first adhesive layer 20A, the polyimide layer 10, and the second adhesive layer 20B are laminated in this order.

[0064] The adhesive layer 100 of this embodiment satisfies the following conditions a to c.

[0065] Condition a) The thickness T1 of the adhesive layer 100 as a whole is in the range of 50 μm or more and 300 μm or less, and the ratio (T2 / T1) of the thickness T2 of the polyimide layer 10 to the thickness T1 of the adhesive layer 100 as a whole is in the range of 0.2 or more and 0.9 or less.

[0066] When the overall thickness T1 of the adhesive layer 100 is less than 50 μm, it is impossible to increase the overall thickness of the resin layer when applied to striplines, thus the effect of reducing transmission loss becomes insufficient. If it exceeds 300 μm, there are concerns that the flexibility required for FPC cannot be guaranteed. From this point of view, the overall thickness T1 of the adhesive layer 100 is in the range of 50 μm or more and 300 μm or less, and more preferably in the range of 50 μm or more and 150 μm or less.

[0067] Furthermore, when the ratio (T2 / T1) of the thickness T2 of the polyimide layer 10 to the overall thickness T1 of the adhesive layer 100 is less than 0.2, dimensional stability decreases. If it exceeds 0.9, the first adhesive layer 20A and the second adhesive layer 20B become too thin, making it difficult to guarantee the adhesion or circuit filling properties required as an adhesive sheet. From this perspective, the thickness ratio (T2 / T1) is preferably in the range of 0.2 to 0.9.

[0068] The moisture absorption rate measured under condition b) after drying at 80°C for 1 hour and conditioning at 23°C and 50%RH for 24 hours was less than 0.4% by weight.

[0069] If the moisture absorption rate exceeds 0.4% by weight, the dielectric loss tangent of the adhesive layer 100 as a whole becomes larger, leading to increased transmission loss when applied to striplines. From this perspective, the moisture absorption rate is preferably 0.4% by weight or less. Furthermore, the overall moisture absorption rate of the adhesive layer 100 can be adjusted using the ratio of the moisture absorption rate and thickness of the polyimide layer 10, the first adhesive layer 20A, and the second adhesive layer 20B.

[0070] Condition c) The storage elastic modulus of the first adhesive layer 20A and the second adhesive layer 20B at 50°C is independently less than 1800 MPa, and the maximum value of the storage elastic modulus at 180°C to 260°C is independently less than 800 MPa.

[0071] The storage modulus of elasticity of the first adhesive layer 20A and the second adhesive layer 20B can mitigate the internal stress during hot pressing of the adhesive layer 100, thereby maintaining dimensional stability after application to the strip. If the storage modulus of elasticity of the first adhesive layer 20A and the second adhesive layer 20B at 50°C exceeds 1800 MPa, the dimensional stability is compromised. From this perspective, the storage modulus of elasticity of the first adhesive layer 20A and the second adhesive layer 20B at 50°C is preferably 1800 MPa or less.

[0072] Furthermore, since the maximum values ​​of the storage elastic modulus of the first adhesive layer 20A and the second adhesive layer 20B in the temperature range of 180°C to 260°C are both 800 MPa or less, warping is less likely to occur after the solder reflow process following circuit fabrication. Preferably, the maximum values ​​of the storage elastic modulus of the first adhesive layer 20A and the second adhesive layer 20B in the temperature range of 180°C to 260°C are both 800 MPa or less.

[0073] The adhesive layer 100 in this embodiment preferably also satisfies the following condition d.

[0074] Condition d) After conditioning for 24 hours under constant temperature and humidity conditions (normal) of 23℃ and 50%RH, the dielectric loss tangent at 10GHz measured by the split column dielectric resonator (SPDR) was below 0.004.

[0075] If the dielectric loss tangent of the adhesive layer 100 as a whole exceeds 0.004 at 10 GHz, then when applied to striplines, electrical signal loss is likely to occur along the high-frequency signal transmission path. From this perspective, the dielectric loss tangent of the adhesive layer 100 as a whole at 10 GHz is more preferably 0.003 or less. Furthermore, there is no particular limitation on the lower limit of the dielectric loss tangent of the adhesive layer 100 as a whole at 10 GHz.

[0076] The adhesive layer 100 in this embodiment preferably also satisfies the following condition e.

[0077] e) The tensile modulus of the polyimide layer 10 is above 5.0 GPa.

[0078] By having such a tensile modulus of elasticity, the polyimide layer 10 can suppress the influence of the coefficients of thermal expansion of the first adhesive layer 20A and the second adhesive layer 20B, thereby further improving the dimensional stability after application to the strip. Furthermore, by setting the tensile modulus of elasticity of the polyimide layer 10 within the aforementioned range, the thickness ratio of the polyimide layer 10 can be relatively reduced, thereby increasing the thickness ratio of the first adhesive layer 20A and the second adhesive layer 20B, which is advantageous from the viewpoint of ensuring adhesion. More preferably, the tensile modulus of elasticity of the polyimide layer 10 is 7.0 GPa or higher.

[0079] (Polyimide layer)

[0080] The polyimide layer 10 preferably contains non-thermoplastic polyimide as a main component of the resin composition, more preferably as 70% by weight or more of the resin composition, further preferably as 90% by weight or more of the resin composition, and most preferably as all of the resin composition. The term "main component of the resin composition" refers to a component contained in an amount exceeding 50% by weight relative to the total resin composition. Furthermore, the term "non-thermoplastic polyimide" generally refers to polyimide that does not exhibit softening or adhesion even when heated, but in this invention, it refers to a stored elastic modulus of 1.0 × 10⁻⁶ at 30°C, as measured using a dynamic viscoelasticity measuring device (dynamic mechanical analyzer, DMA). 9 The storage elastic modulus above Pa and at 350℃ is 1.0 × 10⁻⁶. 8 Polyimides with a strength of Pa or higher. Furthermore, the term "thermoplastic polyimide" generally refers to polyimides whose glass transition temperature (Tg) can be clearly identified; however, in this invention, it refers to polyimides with a storage modulus of elasticity of 1.0 × 10⁻⁶ at 30°C, as measured using DMA. 9 The storage elastic modulus is above Pa and less than 1.0 × 10⁻⁶ at 350°C. 8 Pa is a polyimide. Additionally, when referred to as polyimide in this invention, it also refers to resins containing polymers having an imide group in their molecular structure, such as polyamide imide, polyether imide, polyester imide, polysiloxane imide, and polybenzimidazole imide, in addition to polyimide.

[0081] The non-thermoplastic polyimide constituting the polyimide layer 10 contains tetracarboxylic acid residues and diamine residues. In this invention, a tetracarboxylic acid residue refers to a tetravalent group derived from a tetracarboxylic dianhydride, and a diamine residue refers to a divalent group derived from a diamine compound. When the tetracarboxylic dianhydride and the diamine compound, as raw materials, are reacted in approximately equimolar amounts, the types and molar ratios of the tetracarboxylic acid residues and diamine residues contained in the polyimide can be made to approximately correspond to the types and molar ratios of the raw materials.

[0082] (Tetracarboxylic acid residues)

[0083] The non-thermoplastic polyimide constituting the polyimide layer 10 is preferably a tetracarboxylic acid residue containing at least one tetracarboxylic acid residue derived from 3,3',4,4'-biphenyl tetracarboxylic dianhydride (BPDA) and 1,4-phenylene bis(trimellitic acid monoester) dianhydride (TAHQ), as well as at least one tetracarboxylic acid residue derived from pyromellitic dianhydride (PMDA) and 2,3,6,7-naphthalene tetracarboxylic dianhydride (NTCDA).

[0084] Tetracarboxylic acid residues derived from BPDA (hereinafter also referred to as "BPDA residues") and tetracarboxylic acid residues derived from TAHQ (hereinafter also referred to as "TAHQ residues") readily form ordered structures in polymers, which can reduce dielectric loss tangent or hygroscopicity by inhibiting molecular motion. BPDA residues can impart self-supporting properties to the gel film of polyamic acid, which is a polyimide precursor, but on the other hand, they tend to increase the coefficient of thermal expansion (CTE) after imidization and decrease the glass transition temperature, thereby reducing heat resistance. Based on this view, it is preferable to control the content of BPDA residues and TAHQ residues in the non-thermoplastic polyimide constituting the polyimide layer 10 in a total range preferably of 20 mol% or more and 60 mol% or less, more preferably 40 mol% or more and 50 mol% or less, relative to all tetracarboxylic acid residues. When the total amount of BPDA residues and TAHQ residues is less than 20 mol%, the formation of the ordered structure of the polymer becomes insufficient, the moisture resistance decreases, or the reduction of the dielectric loss tangent becomes insufficient. If it exceeds 60 mol%, in addition to the increase in CTE or the increase in the amount of change in in-plane delay (RO), there is also the concern of reduced heat resistance.

[0085] Furthermore, tetracarboxylic acid residues derived from pyromellitic dianhydride (hereinafter also referred to as "PMDA residues") and tetracarboxylic acid residues derived from 2,3,6,7-naphthalenetetracarboxylic acid dianhydride (hereinafter also referred to as "NTCDA residues") are rigid and therefore play a role in improving in-plane orientation, suppressing CTE, and controlling in-plane delay (RO) or glass transition temperature. On the other hand, PMDA residues have a small molecular weight, so if their amount becomes excessive, the concentration of imide groups in the polymer increases, polar groups increase, and hygroscopicity increases, leading to an increase in dielectric loss tangent due to the influence of moisture within the molecular chain. In addition, NTCDA residues tend to make the film brittle due to the highly rigid naphthalene backbone and increase the elastic modulus. Therefore, it is preferable that the non-thermoplastic polyimide constituting the polyimide layer 10 contains PMDA residues and NTCDA residues in a total range of preferably 40 mol% or more and 80 mol% or less, more preferably 50 mol% or more and 60 mol% or less, and even more preferably 50 mol% to 55 mol% relative to all tetracarboxylic acid residues. When the total amount of PMDA residues and NTCDA residues is less than 40 mol%, there is a concern that the CTE may increase or the heat resistance may decrease. If it exceeds 80 mol%, there is a concern that the concentration of imide groups in the polymer will increase, the polar groups will increase and the low hygroscopicity will be impaired, and the dielectric loss tangent will increase; or there is a concern that the film will become brittle and the self-support of the film will decrease.

[0086] In addition, the total percentage of at least one BPDA residue and TAHQ residue and at least one PMDA residue and NTCDA residue is preferably 80 mol% or more, and more preferably 90 mol% or more, relative to all tetracarboxylic acid residues.

[0087] Other than the BPDA, TAHQ, PMDA, and NTCDA residues contained in the non-thermoplastic polyimide constituting the polyimide layer 10, tetracarboxylic acid residues may be listed, for example, from 3,3',4,4'-diphenylsulfone tetracarboxylic dianhydride, 4,4'-oxyphthalic anhydride, 2,3',3,4'-biphenyltetracarboxylic dianhydride, 2,2',3,3'-benzophenone tetracarboxylic dianhydride, 2,3,3',4'-benzophenone tetracarboxylic dianhydride or 3,3',4,4'-benzophenone tetracarboxylic dianhydride, 2,3',3,4'-diphenyl ether tetracarboxylic dianhydride, bis(2,3-dicarboxyphenyl) ether dianhydride, 3, 3”,4,4”-p-terphenyltetracarboxylic acid dianhydride, 2,3,3”,4”-p-terphenyltetracarboxylic acid dianhydride or 2,2”,3,3”-p-terphenyltetracarboxylic acid dianhydride, 2,2-bis(2,3-dicarboxyphenyl)-propane dianhydride or 2,2-bis(3,4-dicarboxyphenyl)-propane dianhydride, bis(2,3-dicarboxyphenyl)methane dianhydride or bis(3,4-dicarboxyphenyl)methane dianhydride, bis(2,3-dicarboxyphenyl)sulfone dianhydride or bis(3,4-dicarboxyphenyl)sulfone dianhydride, 1,1-bis(2,3-dicarboxyphenyl)ethane dianhydride or 1,1-bis(3,4-dicarboxyphenyl)ethane dianhydride, 1,2,7,8-phenanthrene-tetracarboxylic acid dianhydride Carboxylic acid dianhydrides, 1,2,6,7-phenanthrene-tetracarboxylic acid dianhydrides or 1,2,9,10-phenanthrene-tetracarboxylic acid dianhydrides, 2,3,6,7-anthracene-tetracarboxylic acid dianhydrides, 2,2-bis(3,4-dicarboxyphenyl)tetrafluoropropane dianhydrides, 2,3,5,6-cyclohexane dianhydrides, 1,2,5,6-naphthalene-tetracarboxylic acid dianhydrides, 1,4,5,8-naphthalene-tetracarboxylic acid dianhydrides, 4,8-dimethyl-1,2,3,5,6,7-hexahydronaphthalene-1,2,5,6-tetracarboxylic acid dianhydrides, 2,6-dichloronaphthalene-1,4,5,8-tetracarboxylic acid dianhydrides or 2,7-dichloronaphthalene-1,4,5,8-tetracarboxylic acid dianhydrides, 2,3,6,7- (or 1,4,5,8-) Aromatic tetracarboxylic acid residues derived from tetrachloronaphthalene-1,4,5,8-(or 2,3,6,7-)tetracarboxylic acid dianhydride, 2,3,8,9-perylene-tetracarboxylic acid dianhydride, 3,4,9,10-perylene-tetracarboxylic acid dianhydride, 4,5,10,11-perylene-tetracarboxylic acid dianhydride or 5,6,11,12-perylene-tetracarboxylic acid dianhydride, cyclopentane-1,2,3,4-tetracarboxylic acid dianhydride, pyrazine-2,3,5,6-tetracarboxylic acid dianhydride, pyrrolidine-2,3,4,5-tetracarboxylic acid dianhydride, thiophene-2,3,4,5-tetracarboxylic acid dianhydride, 4,4'-bis(2,3-dicarboxyphenoxy)diphenylmethane dianhydride, ethylene glycol bis(triphenylene oxide) anhydride, etc.

[0088] (diamine residues)

[0089] The diamine residue contained in the non-thermoplastic polyimide constituting the polyimide layer 10 is preferably a diamine residue derived from a diamine compound represented by the general formula (A1).

[0090] [Chemistry 2]

[0091]

[0092] In formula (A1), the linker Z represents a single bond or -COO-, Y independently represents a monovalent hydrocarbon group with 1 to 3 carbon atoms that can be substituted with a halogen atom or a phenyl group, or an alkoxy group with 1 to 3 carbon atoms, or a perfluoroalkyl group or alkenyl group with 1 to 3 carbon atoms, n represents an integer from 0 to 2, and p and q independently represent integers from 0 to 4. Here, "independently" means that the multiple substituents Y, and the integers p and q in the formula (A1) can be the same or different. Furthermore, in the formula (A1), the hydrogen atoms in the two terminal amino groups can be substituted, for example, they can also be -NR2R3 (here, R2 and R3 independently refer to any substituent such as an alkyl group).

[0093] The diamine compound represented by the general formula (A1) (hereinafter sometimes referred to as "diamine (A1)") is an aromatic diamine having one or more benzene rings. Due to its rigid structure, the diamine (A1) imparts an ordered structure to the polymer as a whole. Therefore, polyimides with low air permeability and low moisture absorption can be obtained, reducing the moisture content within the molecular chain and thus lowering the dielectric loss tangent. Here, the linking group Z is preferably a single bond.

[0094] Examples of diamines (A1) include: 1,4-diaminobenzene (p-PDA (p-phenylenediamine); p-phenylenediamine), 2,2'-dimethyl-4,4'-diaminobiphenyl (m-TB), 2,2'-n-propyl-4,4'-diaminobiphenyl (m-NPB), and 4-aminophenyl-4'-aminobenzoate (APAB). Among these, 2,2'-dimethyl-4,4'-diaminobiphenyl (m-TB) is the most preferred.

[0095] The non-thermoplastic polyimide constituting the polyimide layer 10 preferably contains at least 50 mol% of diamine residues derived from diamine (Al), more preferably at least 80 mol% and even more preferably at least 85 mol% relative to all diamine residues. By using diamine (Al) in amounts within the aforementioned range, and by utilizing the rigid structure derived from the monomer, an ordered structure can be easily formed in the polymer as a whole, thus readily obtaining a non-thermoplastic polyimide with low air permeability, low moisture absorption, and low dielectric loss tangent. From this perspective, it is most preferable to contain residues derived from 2,2'-dimethyl-4,4'-diaminobiphenyl (m-TB) in the range of 90 mol% to 100 mol% relative to all diamine residues.

[0096] Other diamine residues contained in the non-thermoplastic polyimide constituting the polyimide layer 10 are not particularly limited if they are residues derived from diamine compounds used as raw materials for polyimides. Examples include: 1,3-bis(4-aminophenoxy)benzene (TPE-R), 1,3-bis(3-aminophenoxy)benzene (APB), 4,4'-[2-methyl-(1,3-phenylene)dioxy]bisaniline, 4,4'-[4-methyl-(1,3-phenylene)dioxy]bisaniline, 4,4'-[ 5-Methyl-(1,3-phenylene)dioxy]bisaniline, 2,2-bis-[4-(3-aminophenoxy)phenyl]propane, bis[4-(3-aminophenoxy)phenyl]sulfone, bis[4-(3-aminophenoxy)]biphenyl, bis[1-(3-aminophenoxy)]biphenyl, bis[4-(3-aminophenoxy)phenyl]methane, bis[4-(3-aminophenoxy)phenyl]ether, bis[4-(3-aminophenoxy)]benzophenone, 9,9-bis[4-(3-aminophenoxy)phenyl]fluorene, 2,2-bis-[4-(4-aminophenoxy)phenyl]hexafluoropropane, 2,2-bis-[4-(3-aminophenoxy)phenyl]hexafluoropropane, 3,3'-dimethyl-4, 4'-Diaminobiphenyl, 4,4'-methylenedi-o-toluidine, 4,4'-methylenedi-2,6-ditoluidine, 4,4'-methylene-2,6-diethylaniline, 3,3'-diaminodiphenylethane, 3,3'-diaminobiphenyl, 3,3'-dimethoxybiphenyl, 3,3”-diamino-p-terphenyl, 4,4'-[1,4-phenylenebis(1-methylethylene)]bisaniline, 4,4'-[1,3-phenylenebis(1-methylethylene)]bisaniline, bis(p-aminocyclohexyl)methane, bis(p-β-amino-tert-butylphenyl) ether, bis(p-β-methyl-δ-aminopentyl)benzene, p-bis(2-methyl-4 ...methyl-4-aminopentyl)benzene, p-bis(2-methyl-4-methyl-4-aminopentyl)benzene, p-bis(2-methyl-4-methyl-4-aminopentyl)benzene, p-bis(2-methyl-4-methyl-4-aminopentyl)benzene, p-bis(2-methyl-4-methyl-4-methyl-4-methyl-4-methyl-4-methyl-4-methyl-4-methyl-4-methyl-4-methyl-4-methyl (1,1-Dimethyl-5-aminopentyl)benzene, 1,5-diaminonaphthalene, 2,6-diaminonaphthalene, 2,4-bis(β-amino-tert-butyl)toluene, 2,4-diaminotoluene, m-xylene-2,5-diamine, p-xylene-2,5-diamine, m-xylenediamine, p-xylenediamine, 2,6-diaminopyridine, 2,5-diaminopyridine, 2,5-diamino-1,3,4-oxadiazole, piperazine, 2'-methoxy-4,4'-diaminobenzoylaniline, 4,4'-diaminobenzoylaniline, 1,3-bis[2-(4-aminophenyl)-2-propyl]benzene, 6-amino-2-(4-aminophenoxy)benzoxazole and other aromatic diamine compounds derived diamine residues;Diamine residues derived from aliphatic diamine compounds, such as dimer acid-type diamines, which are formed by replacing the two terminal carboxylic acid groups of a dimer acid with primary aminomethyl or amino groups.

[0097] By selecting the types of tetracarboxylic acid residues and diamine residues in the non-thermoplastic polyimide, or by using the molar ratio of two or more tetracarboxylic acid residues or diamine residues, the coefficient of thermal expansion, storage modulus of elasticity, tensile modulus of elasticity, etc., can be controlled. Furthermore, when multiple polyimide structural units are present in the non-thermoplastic polyimide, they can exist in a block form or randomly, preferably randomly.

[0098] Furthermore, by setting both the tetracarboxylic acid residues and diamine residues contained in the non-thermoplastic polyimide as aromatic groups, the dimensional accuracy of the polyimide film under high-temperature conditions can be improved, and therefore it is preferred.

[0099] (Synthesis of polyimide)

[0100] Non-thermoplastic polyimides can be manufactured by reacting the acid anhydride and diamine in a solvent to generate a precursor resin, followed by heating to close the ring. For example, a polymerization reaction is carried out by dissolving the acid anhydride and diamine components in an approximately equimolar amount in an organic solvent and stirring at a temperature ranging from 0°C to 100°C for 30 minutes to 24 hours, thereby obtaining polyamic acid as a precursor for polyimides. During the reaction, the reactants are dissolved in the organic solvent at a concentration of 5% to 30% by weight, preferably 10% to 20% by weight. Examples of organic solvents used in the polymerization reaction include: N,N-dimethylformamide, N,N-dimethylacetamide (DMAc), N-methyl-2-pyrrolidone, 2-butanone, dimethyl sulfoxide, dimethyl sulfate, cyclohexanone, dioxane, tetrahydrofuran, diethylene glycol dimethyl ether, triethylene glycol dimethyl ether, etc. These solvents can also be used in combination with two or more, and can further be used with aromatic hydrocarbons such as xylene and toluene. In addition, there is no particular limitation on the amount of this organic solvent used, but it is preferable to adjust the concentration of the polyamic acid solution (polyimide precursor solution) obtained by the polymerization reaction to about 5% to 30% by weight.

[0101] In the synthesis of polyimide, the acid anhydride and diamine can be used individually or in combination. By selecting the types of acid anhydride and diamine, and the molar ratio of each when using two or more acid anhydrides or diamines, the dielectric properties, thermal expansion, glass transition temperature, etc., can be controlled.

[0102] The synthesized precursor is generally advantageously used as a reaction solvent solution, but can be concentrated, diluted, or replaced with other organic solvents as needed. Furthermore, the precursor generally has excellent solvent solubility, thus making its use advantageous. There are no particular limitations on the method of imidizing the precursor; for example, heat treatment is preferably performed in the solvent at a temperature ranging from 80°C to 400°C for 1 hour to 24 hours.

[0103] The imide concentration of the non-thermoplastic polyimide is preferably 37% by weight or less, more preferably 33% by weight or less, and even more preferably 32% by weight or less. Here, "imide concentration" refers to the value obtained by dividing the molecular weight of the imide group (-(CO)2-N-) in the polyimide by the molecular weight of the overall structure of the polyimide. If the imide concentration exceeds 37% by weight, the molecular weight of the resin itself decreases, and the low hygroscopicity deteriorates due to the increase in polar groups. By selecting the combination of the anhydride and diamine compound to control the molecular orientation in the non-thermoplastic polyimide, the increase in CTE accompanying the decrease in imide concentration is suppressed, thus ensuring low hygroscopicity.

[0104] The weight-average molecular weight of the non-thermoplastic polyimide is preferably in the range of 10,000 to 400,000, and more preferably in the range of 50,000 to 350,000. If the weight-average molecular weight is less than 10,000, the strength of the adhesive layer 100 tends to decrease. On the other hand, if the weight-average molecular weight exceeds 400,000, the viscosity tends to increase excessively, which can easily lead to defects such as uneven film thickness and streaks during coating operations.

[0105] From the viewpoint of ensuring insulation, maintaining mechanical strength, and other functions as a base layer in the adhesive layer 100, and considering the handlingability during the manufacture of the adhesive layer 100, the thickness of the polyimide layer 10 is preferably in the range of 10 μm or more and 135 μm or less, more preferably in the range of 12 μm or more and 50 μm or less. If the thickness of the polyimide layer 10 is less than the lower limit, the electrical insulation or processability becomes insufficient; if it exceeds the upper limit, productivity decreases.

[0106] From the viewpoint of heat resistance, the glass transition temperature (Tg) of the polyimide layer 10 is preferably 280°C or higher. By having a glass transition temperature (Tg) of 280°C or higher for the polyimide layer 10, dimensional stability can be maintained during heating processes such as welding.

[0107] From the viewpoint of improving the dimensional stability of the adhesive layer 100 and suppressing warping, the coefficient of thermal expansion of the polyimide layer 10 is preferably in the range of 1 ppm / K or more and 30 ppm / K or less, more preferably in the range of 1 ppm / K or more and 25 ppm / K or less, and even more preferably in the range of 15 ppm / K or more and 25 ppm / K or less.

[0108] The polyimide layer 10 is preferably conditioned for 24 hours under constant temperature and humidity conditions (normal) at 23°C and 50% RH, and the dielectric loss tangent at 10 GHz, as measured by a split column dielectric resonator (SPDR), is 0.006 or less. By ensuring that the dielectric loss tangent of the polyimide layer 10 at 10 GHz is 0.006 or less, the overall dielectric loss tangent of the adhesive layer 100 can be reduced. If the dielectric loss tangent of the polyimide layer 10 at 10 GHz exceeds 0.006, it becomes difficult to suppress the overall dielectric loss tangent of the adhesive layer 100 to a low level.

[0109] In the polyimide layer 10, other curing resin components such as plasticizers, epoxy resins, curing agents, curing accelerators, coupling agents, fillers, flame retardants, etc., can be appropriately formulated as any component.

[0110] (First adhesive layer / Second adhesive layer)

[0111] The materials of the first adhesive layer 20A and the second adhesive layer 20B are not particularly limited as long as condition c is met, and they can be independently composed of thermoplastic resins or thermosetting resins. Examples of such resins include: polyimide resins, polyamide resins, epoxy resins, phenoxy resins, acrylic resins, polyurethane resins, styrene resins, polyester resins (including liquid crystal polyester resins), phenolic resins, polysulfone resins, polyethersulfone resins, polyphenylene sulfide resins, polyethylene resins, polypropylene resins, silicone resins, polyetherketone resins, polyvinyl alcohol resins, polyvinyl butyral resins, styrene-maleimide copolymers, maleimide-vinyl compound copolymers, or (meth)acrylic acid copolymers, benzoxazine resins, bismaleimide resins, cyanate ester resins, etc. Resins that meet condition c can be selected from these, or the design can be tailored to meet condition c, to be used as the first adhesive layer 20A and the second adhesive layer 20B. When the first adhesive layer 20A and the second adhesive layer 20B are thermosetting resins, they may contain organic peroxides, hardeners, and curing accelerators. Depending on the requirements, hardeners and curing accelerators, or catalysts and co-catalysts, may also be used in combination. The amount of hardener, curing accelerator, catalyst, co-catalyst, and organic peroxide added, as well as whether they are added, can be determined as long as they are within the range that condition c is met.

[0112] The resin constituting the first adhesive layer 20A and the second adhesive layer 20B is preferably a resin containing polyimide as a main component of the resin, preferably containing 70% by weight or more, more preferably 90% by weight or more, and most preferably all of the resin component as the resin component. Furthermore, the term "main component of the resin" refers to a component contained in an amount exceeding 50% by weight relative to the total resin component. As a preferred polyimide for forming the first adhesive layer 20A and the second adhesive layer 20B based on satisfying condition c, a polyimide (hereinafter sometimes referred to as "adhesive polyimide") is preferably a polyimide containing anhydride residues derived from a tetracarboxylic anhydride component and diamine residues derived from a diamine component, and containing 50 mol% or more of diamine residues derived from a dimer diamine composition relative to all diamine residues, wherein the dimer diamine composition is a dimer diamine whose main component is a dimer diamine in which the two terminal carboxylic acid groups of a dimer acid are replaced with primary aminomethyl or amino groups. In other words, the adhesive polyimide is obtained by using a dimer diamine composition whose main component is a dimer diamine, which contains at least 50 mol% relative to the total diamine content and in which the two terminal carboxylic acid groups of the dimer acid are replaced with primary aminomethyl or amino groups. By setting the content of diamine residues derived from the dimer diamine composition to preferably be at least 50 mol%, more preferably at least 70 mol%, and even more preferably in the range of 80 mol% to 99 mol% relative to the total diamine residues, condition c can be satisfied and the relative permittivity and dielectric loss tangent can be reduced. That is, by containing diamine residues derived from the dimer diamine composition in the aforementioned amount, the hot-pressing properties can be improved by lowering the glass transition temperature (lower Tg) of the polyimide and the internal stress can be mitigated by lowering the elastic modulus. In addition, when the content of diamine residues derived from the dimer diamine composition is less than 50 mol%, the polar groups contained in the polyimide are relatively increased, thereby making it easier to increase the relative permittivity and dielectric loss tangent.

[0113] The dimer diamine composition is a refined product containing component (a) as the main component, and the amounts of components (b) and (c) are controlled.

[0114] (a) Dimeric diamine;

[0115] The dimer diamine of component (a) refers to a diamine formed by replacing the two terminal carboxylic acid groups (-COOH) of a dimer acid with primary aminomethyl (-CH2-NH2) or amino (-NH2). Dimer acids are known dicarboxylic acids obtained through intermolecular polymerization of unsaturated fatty acids. Their industrial manufacturing process is largely standardized in the industry, and they can be obtained by dimerizing unsaturated fatty acids with 11 to 22 carbon atoms using clay catalysts, etc. The dimer acids obtained industrially are mainly 36-carbon dicarboxylic acids obtained by dimerizing 18-carbon unsaturated fatty acids such as oleic acid, linoleic acid, and linolenic acid. However, depending on the degree of purification, they may contain arbitrary amounts of monomeric acids (18 carbon atoms), trimeric acids (54 carbon atoms), and other polymeric fatty acids with 20 to 54 carbon atoms. In addition, double bonds remain after the dimerization reaction, but in this invention, it is assumed that the dimer acid also contains compounds that undergo hydrogenation to reduce the degree of unsaturation. (a) The dimer diamine of component (a) can be defined as a diamine compound obtained by replacing the terminal carboxylic acid group of a dicarboxylic acid compound with a carbon number in the range of 18 to 54, preferably in the range of 22 to 44, with a primary aminomethyl or amino group.

[0116] As a characteristic of dimerized diamines, they can impart properties derived from the dimer acid backbone. Specifically, dimerized diamines are large aliphatic molecules with molecular weights of approximately 560–620, thus increasing the molar volume of the molecule and relatively reducing the polar groups in the polyimide. This characteristic of dimer acid-type diamines is believed to help suppress the decrease in the heat resistance of polyimides, while simultaneously reducing the relative dielectric constant and dielectric loss tangent, thereby improving dielectric properties. Furthermore, due to the presence of two freely moving hydrophobic chains with 7–9 carbon atoms and two chain-like aliphatic amino groups with a length close to 18 carbon atoms, not only can polyimides be endowed with flexibility, but they can also be configured with asymmetric or non-planar chemical structures, thus enabling the lower dielectric constant of polyimides.

[0117] The dimer diamine composition preferably uses a dimer diamine composition in which the content of dimer diamine in component (a) is increased to 96% by weight or more, preferably 97% by weight or more, and more preferably 98% by weight or more, through purification methods such as molecular distillation. By setting the content of dimer diamine in component (a) to 96% by weight or more, the expansion of the molecular weight distribution of the polyimide can be suppressed. Furthermore, if technically feasible, it is optimal that the dimer diamine composition is entirely (100% by weight) composed of dimer diamine in component (a).

[0118] (b) Monoamine compounds obtained by replacing the terminal carboxylic acid group of a monocarboxylic acid compound with a carbon number in the range of 10 to 40 with a primary aminomethyl or amino group.

[0119] Monocarboxylic acid compounds with 10 to 40 carbon atoms are mixtures derived from monounsaturated fatty acids with 10 to 20 carbon atoms from the raw materials of dimer acids, and monocarboxylic acid compounds with 21 to 40 carbon atoms that are byproducts of dimer acid production. Monoamine compounds are obtained by replacing the terminal carboxylic acid group of these monocarboxylic acid compounds with a primary aminomethyl or amino group.

[0120] (b) The monoamine compound of the component is a component that inhibits the increase in molecular weight of the polyimide. During the polymerization of the polyamic acid or the polyimide, the monofunctional amino group of the monoamine compound reacts with the terminal anhydride group of the polyamic acid or the polyimide, thereby sealing the terminal anhydride group and inhibiting the increase in molecular weight of the polyamic acid or the polyimide.

[0121] (c) An amine compound obtained by replacing the terminal carboxylic acid group of a polyacid compound having a hydrocarbon group in the range of 41 to 80 carbons with a primary aminomethyl or amino group (except for the dimer diamine);

[0122] Polybasic acid compounds with hydrocarbon groups having 41 to 80 carbon atoms are primarily composed of tribasic acid compounds with 41 to 80 carbon atoms, which are byproducts of the production of dimer acids. They may also include polymeric fatty acids other than dimer acids with 41 to 80 carbon atoms. Amine compounds are obtained by replacing the terminal carboxylic acid group of these polybasic acid compounds with a primary aminomethyl or amino group.

[0123] (c) The amine compounds in component (c) contribute to the increase in the molecular weight of polyimides. The reaction of trifunctional or higher amino groups, with the triamine derived from a trimeric acid as the main component, with the terminal anhydride group of the polyamic acid or polyimide results in a sharp increase in the molecular weight of the polyimide. Additionally, amine compounds derived from polymeric fatty acids other than dimer acids with 41 to 80 carbon atoms also contribute to the increase in the molecular weight of polyimides, thus causing the gelation of polyamic acids or polyimides.

[0124] When quantifying each component using gel permeation chromatography (GPC), to easily identify the peak start, peak top, and peak end of each component in the dimer diamine composition, a sample prepared by treating the dimer diamine composition with acetic anhydride and pyridine was used, with cyclohexanone as an internal standard. Using the sample prepared as described above, each component was quantified using the area percentage of the GPC chromatogram. The peak start and peak end of each component were set as the minimum values ​​of the respective peak curves, and these values ​​were used as a reference for calculating the area percentage of the chromatogram.

[0125] Furthermore, the dimer diamine composition, based on the area percentage of the chromatogram obtained by GPC determination, preferably has a total content of 4% or less, and more preferably less than 4%, of components (b) and (c). By setting the total content of components (b) and (c) to 4% or less, the expansion of the molecular weight distribution of the polyimide can be suppressed.

[0126] Furthermore, the area percentage of the chromatogram of component (b) is preferably 3% or less, more preferably 2% or less, and even more preferably 1% or less. By setting it within this range, the decrease in the molecular weight of the polyimide can be suppressed, thereby expanding the range of the molar ratio of the tetracarboxylic anhydride component and the diamine component. Moreover, component (b) may also be excluded from the dimer diamine composition.

[0127] Furthermore, the area percentage of the chromatogram of component (c) is 2% or less, preferably 1.8% or less, and more preferably 1.5% or less. By setting it within this range, the sharp increase in the molecular weight of the polyimide can be suppressed, thereby suppressing the increase in the dielectric loss tangent of the resin film across a wide frequency range. Moreover, component (c) may not be included in the dimer diamine composition.

[0128] Furthermore, when the area percentage ratio (b / c) of the chromatograms of components (b) and (c) is 1 or more, the molar ratio of the tetracarboxylic anhydride component and the diamine component (tetracarboxylic anhydride component / diamine component) is preferably set to 0.97 or more and less than 1.0. By setting this molar ratio, it is easier to control the molecular weight of the polyimide.

[0129] Furthermore, if the ratio of the area percentages of the chromatograms of components (b) and (c) is less than 1, the molar ratio of the tetracarboxylic anhydride component and the diamine component (tetracarboxylic anhydride component / diamine component) is preferably set to 0.97 or more and 1.1 or less. By setting this molar ratio, it is easier to control the molecular weight of the polyimide.

[0130] The dimer diamine composition can be made from commercially available products, preferably refined to reduce components other than the dimer diamine in component (a), for example, preferably setting component (a) to 96% or more in area. There are no particular limitations on the refining method; known methods such as distillation or precipitation refining are preferred. Examples of commercially available dimer diamine compositions include PRIAMINE 1073 (trade name), PRIAMINE 1074 (trade name), and PRIAMINE 1075 (trade name) manufactured by Croda Japan.

[0131] The synthesis of adhesive polyimides can be carried out according to the methods described in the non-thermoplastic polyimides.

[0132] When an adhesive polyimide has a ketone group within its molecule, the ketone group reacts with an amino group of an amino compound (hereinafter sometimes referred to as "crosslinking-forming amino compound") having at least two primary amino groups as functional groups to form a C=N bond, thereby forming a crosslinked structure. This type of polyimide with a crosslinked structure (hereinafter sometimes referred to as "crosslinked polyimide") is an example of the application of adhesive polyimides and is considered a preferred form. By forming a crosslinked structure, the heat resistance of the adhesive polyimide can be improved. Preferred tetracarboxylic dianhydrides for forming adhesive polyimides with ketone groups include, for example, 3,3',4,4'-benzophenone tetracarboxylic dianhydride (BTDA). As diamine compounds, examples include, for example, 4,4'-bis(3-aminophenoxy)benzophenone (BABP) and 1,3-bis[4-(3-aminophenoxy)benzoyl]benzene (BABB), and other aromatic diamines. For the purpose of forming a crosslinking structure, it is particularly preferred that the adhesive polyimide contains, with a crosslinking-forming amino compound acting on it, preferably 50 mol% or more, more preferably 60 mol% or more of BTDA residues derived from BTDA relative to all tetracarboxylic acid residues. Furthermore, in this invention, "BTDA residue" refers to a tetravalent group derived from BTDA.

[0133] Examples of amino compounds used for crosslinking formation include: (I) dihydrazide compounds, (II) aromatic diamines, and (III) aliphatic amines. Among these, dihydrazide compounds are preferred. Aliphatic amines other than dihydrazide compounds readily form crosslinked structures even at room temperature, raising concerns about the shelf life of the varnish. On the other hand, aromatic diamines require high temperatures to form crosslinked structures. As described above, using dihydrazide compounds allows for both improved shelf life of the varnish and a shorter curing time. Preferred diacylhydrazides include, for example, oxalate diacylhydrazide, malonate diacylhydrazide, succinate diacylhydrazide, glutarate diacylhydrazide, adipate diacylhydrazide, pimecrolate diacylhydrazide, octanoate diacylhydrazide, azelaate diacylhydrazide, sebacylhydrazide, dodecanoate diacylhydrazide, maleate diacylhydrazide, fumarate diacylhydrazide, diethylene glycol diacylhydrazide, tartrate diacylhydrazide, malate diacylhydrazide, phthalate diacylhydrazide, isophthalate diacylhydrazide, terephthalate diacylhydrazide, 2,6-naphthoic acid diacylhydrazide, 4,4-bisphenyl diacylhydrazide, 1,4-naphthoic acid diacylhydrazide, 2,6-pyridine diacylhydrazide, itaconic acid diacylhydrazide, etc. These diacylhydrazides can be used alone or in combination of two or more.

[0134] In addition, the amino compounds such as (I) dihydrazide compounds, (II) aromatic diamines, and (III) aliphatic amines can also be used in combinations beyond the scope of (I) and (II), (I) and (III), or (I) and (II) and (III).

[0135] Furthermore, from the viewpoint of making the network structure formed by crosslinking using an amino compound for crosslinking more compact, the molecular weight (weight average molecular weight if the amino compound for crosslinking is an oligomer) of the amino compound for crosslinking used in this invention is preferably 5,000 or less, more preferably 90 to 2,000, and even more preferably 100 to 1,500. Particularly preferred are amino compounds for crosslinking with a molecular weight of 100 to 1,000. If the molecular weight of the amino compound for crosslinking is less than 90, one amino group of the amino compound is limited to forming a C=N bond with the ketone group of the adhesive polyimide, and the peripheral volume of the remaining amino group becomes larger, thus there is a tendency for the remaining amino group to have difficulty forming a C=N bond.

[0136] In the case where the ketone groups in the adhesive polyimide are crosslinked with an amino compound for crosslinking, the amino compound for crosslinking is added to a resin solution containing the adhesive polyimide, causing the ketone groups in the adhesive polyimide to undergo a condensation reaction with the primary amino groups of the amino compound for crosslinking. Through this condensation reaction, the resin solution is cured to form a cured product. In this case, the amount of the amino compound for crosslinking can be set as follows: relative to 1 mole of ketone groups, the total amount of primary amino groups is 0.004 mol to 1.5 mol, preferably 0.005 mol to 1.2 mol, more preferably 0.03 mol to 0.9 mol, and most preferably 0.04 mol to 0.6 mol. When the amount of crosslinking-forming amino compound added is less than 0.004 moles relative to 1 mole of ketone group, the crosslinking using the crosslinking-forming amino compound is insufficient, and therefore there is a tendency for it to be difficult to exhibit heat resistance after curing. If the amount of crosslinking-forming amino compound added exceeds 1.5 moles, the unreacted crosslinking-forming amino compound acts as a thermoplasticizer, which tends to reduce the heat resistance of the adhesive layer.

[0137] The conditions for the condensation reaction used to form crosslinks are not particularly limited if the ketone group in the adhesive polyimide reacts with the primary amino group of the amino compound used for crosslinking to form an imine bond (C=N bond). Regarding the temperature for the heating condensation, for reasons such as releasing the water generated during condensation from the system or simplifying the condensation process when a heating condensation reaction is subsequently performed after the synthesis of the adhesive polyimide, a range of 120°C to 220°C is preferred, and a range of 140°C to 200°C is more preferred. The reaction time is preferably about 30 minutes to 24 hours. The endpoint of the reaction can be determined, for example, by measuring the infrared absorption spectrum using a Fourier transform infrared spectrophotometer (commercially available: FT / IR620 manufactured by Nippon Spectrophotometer) and using a 1670 cm⁻¹ spectral density. -1 The reduction or disappearance of the absorption peak originating from the ketone groups in the nearby polyimide resin, and 1635 cm⁻¹ -1 The presence of a nearby absorption peak originating from an imine group confirms this.

[0138] The thermal condensation of the ketone group of the adhesive polyimide with the primary amino group of the crosslinking-forming amino compound can be carried out, for example, by the following methods:

[0139] (1) A method of adding an amino compound for crosslinking formation and heating immediately following the synthesis (imidization) of adhesive polyimide;

[0140] (2) An excess of amino compound is added in advance as a diamine component, followed by the synthesis (imidization) of adhesive polyimide, while the remaining amino compound that does not participate in imidization or amidation is used as an amino compound for crosslinking formation and heated together with adhesive polyimide.

[0141] or

[0142] (3) A method of heating the composition of adhesive polyimide containing the amino compound for crosslinking formation after it has been processed into a specified shape (e.g., after being coated on any substrate or after being formed into a film).

[0143] To impart heat resistance to adhesive polyimides, examples of cross-linked polyimides that form a cross-linked structure by forming imine bonds have been given, but this is not a limitation. As a method of curing polyimides, compounds with unsaturated bonds, such as epoxy resins, epoxy resin curing agents, maleimides, activated ester resins, and resins with a styrene backbone, can also be formulated for curing.

[0144] The glass transition temperatures (Tg) of the first adhesive layer 20A and the second adhesive layer 20B are both below 180°C, preferably below 160°C. By setting the Tg of the first adhesive layer 20A and the second adhesive layer 20B to below 180°C, low-temperature hot pressing can be performed, thus mitigating internal stress generated during lamination and suppressing dimensional changes after circuit fabrication. If the Tg of the first adhesive layer 20A and the second adhesive layer 20B exceeds 180°C, the temperature required for bonding between insulating resin layers for use in striplines becomes higher, raising concerns about compromising the dimensional stability of the striplines.

[0145] The first adhesive layer 20A and the second adhesive layer 20B are preferably conditioned for 24 hours under constant temperature and humidity conditions (normal environment) at 23°C and 50% RH, and the dielectric loss tangent at 10 GHz, as measured by a split column dielectric resonator (SPDR), is 0.004 or less. By ensuring that the dielectric loss tangent of the first adhesive layer 20A and the second adhesive layer 20B is 0.004 or less at 10 GHz, the overall dielectric loss tangent of the adhesive layer 100 can be reduced. If the dielectric loss tangent of the polyimide layer 10 at 10 GHz exceeds 0.004, it becomes difficult to suppress the overall dielectric loss tangent of the adhesive layer 100 to a low level.

[0146] In the first adhesive layer 20A and the second adhesive layer 20B, other curing resin components such as plasticizers and epoxy resins, as well as curing agents, curing accelerators, coupling agents, fillers, flame retardants, etc., can be appropriately formulated as any components.

[0147] The adhesive layer 100 may be manufactured, for example, by method 1 or method 2.

[0148] [Method 1]

[0149] A polyimide film corresponding to the polyimide layer 10 constituting adhesive layer 100 and an adhesive film corresponding to the first adhesive layer 20A and the second adhesive layer 20B are prepared separately. Then, the polyimide film is sandwiched between the two adhesive films, and hot-pressed at a temperature, for example, exceeding the glass transition temperature of the resins constituting the first adhesive layer 20A and the second adhesive layer 20B, thereby producing an adhesive layer 100 with a three-layer structure.

[0150] [Method 2]

[0151] First, a polyimide film corresponding to the polyimide layer 10 is prepared using conventional methods. A resin solution constituting the first adhesive layer 20A is coated onto one side of the polyimide film to a predetermined thickness. The coated film is then heated to form the first adhesive layer 20A. Next, a resin solution constituting the second adhesive layer 20B is coated onto the other side of the polyimide film to a predetermined thickness. The coated film is then heated and dried to form the second adhesive layer 20B. Thus, an adhesive layer 100 with a three-layer structure can be manufactured.

[0152] The polyimide film or adhesive film used in methods 1 and 2 can be manufactured, for example, by coating a resin solution onto any supporting substrate, drying it, and then peeling it off from the supporting substrate. Furthermore, there are no particular limitations on the method for coating the resin solution onto the supporting substrate or polyimide film; for example, a notched roller coater, a die coater, a doctor blade coater, or a die lip coater can be used.

[0153] [Circuit board]

[0154] The adhesive layer 100 is primarily used as a circuit board material for FPCs, rigid / flexible circuit boards, and other similar applications. For example, a circuit board with a metal clad laminate having an insulating resin layer and a metal layer, or a circuit board whose metal layer is patterned using conventional methods to form a wiring layer, can be integrated by inserting the adhesive layer 100 between two or more metal clad laminates and / or circuit boards and heat-pressing them together. This allows for the manufacture of a multi-layered circuit board. As an example of such a circuit board, a stripline used as a high-frequency transmission path can be cited.

[0155] (band)

[0156] Figure 2 This is a schematic diagram illustrating the cross-sectional structure of the stripline, which is a preferred form of the circuit board of the present invention. Figure 2 The stripline 200 shown includes: a first metal layer 30A; a first insulating resin layer 40A, comprising one or more layers stacked on one side of the first metal layer 30A; and a wiring layer 50, grounded to the first insulating resin layer 40A. Here, the first metal layer 30A, the first insulating resin layer 40A, and the wiring layer 50 form a first laminate 60A.

[0157] Additionally, the strip 200 includes a second metal layer 30B and a second insulating resin layer 40B, wherein the second insulating resin layer 40B comprises one or more layers stacked on one side of the second metal layer 30B. Here, the second metal layer 30B and the second insulating resin layer 40B form a second laminate 60B.

[0158] Furthermore, the strip 200 includes an intermediate resin layer 101 that is stacked between the first insulating resin layer 40A and the second insulating resin layer 40B.

[0159] The intermediate resin layer 101 of the stripline 200 is formed by the adhesive layer 100. That is, an intermediate resin layer 101 containing the adhesive layer 100 is interposed between the first laminate 60A and the second laminate 60B, and the layers are laminated such that the first adhesive layer 20A of the adhesive layer 100 is bonded to the first insulating resin layer 40A and the wiring layer 50 of the first laminate 60A, and the second adhesive layer 20B of the adhesive layer 100 is bonded to the second insulating resin layer 40B of the second laminate 60B. The first adhesive layer 20A of the adhesive layer 100 covers the wiring layer 50. That is, the wiring layer 50, which protrudes from the first insulating resin layer 40A, is embedded in the first adhesive layer 20A.

[0160] In the stripline 200, the first metal layer 30A and the second metal layer 30B function as grounding layers or shielding layers. Additionally, in the stripline 200, the wiring layer 50 is patterned to function as a signal line. There are no particular limitations on the materials used for the first metal layer 30A, the second metal layer 30B, and the wiring layer 50; examples include copper, stainless steel, iron, nickel, beryllium, aluminum, zinc, indium, silver, gold, tin, zirconium, tantalum, titanium, lead, magnesium, manganese, and alloys thereof. Copper or copper alloys are particularly preferred. Furthermore, when using copper foil, rolled copper foil or electrolytic copper foil can be used.

[0161] In the strip 200, the first insulating resin layer 40A and the second insulating resin layer 40B are not particularly limited in that they are made of electrically insulating resins, and can be made of thermoplastic resins or thermosetting resins independently. Examples of such resins include: polyimide resins, polyamide resins, epoxy resins, phenoxy resins, acrylic resins, polyurethane resins, styrene resins, polyester resins (including liquid crystal polyester resins), phenolic resins, polysulfone resins, polyethersulfone resins, polyphenylene sulfide resins, polyethylene resins, polypropylene resins, silicone resins, polyetherketone resins, polyvinyl alcohol resins, polyvinyl butyral resins, styrene-maleimide copolymers, maleimide-vinyl compound copolymers, or (meth)acrylic acid copolymers, benzoxazine resins, bismaleimide resins, cyanate ester resins, etc.

[0162] In addition, the first insulating resin layer 40A and the second insulating resin layer 40B are not limited to a single layer, but may also consist of multiple resin layers.

[0163] The thickness or thickness ratio of each layer constituting the stripline 200 can be appropriately set according to the purpose. However, by including an adhesive layer 100 with excellent dimensional stability, low moisture absorption, and a low dielectric loss tangent, reliability based on high dimensional stability can be improved, and transmission loss of high-frequency signals can be suppressed. In particular, in the stripline 200, the first adhesive layer 20A is filled around the wiring layer 50. With this characteristic structure, when using a resin material with a low dielectric loss tangent (e.g., the adhesive polyimide) as the first adhesive layer 20A, excellent transmission loss reduction can be expected. Furthermore, by including the adhesive layer 100 in the stripline 200, unlike the case where adhesive sheets are used, problems such as cutting and grooving damage during laser processing or resin leakage during welding processes can be avoided.

[0164] The strip 200 can be manufactured by separately manufacturing the first laminate 60A and the second laminate 60B using conventional methods, and then bonding them together using a separately prepared adhesive layer 100. That is, it can be manufactured by arranging the first insulating resin layer 40A and wiring layer 50 of the first laminate 60A facing the first adhesive layer 20A of the adhesive layer 100, and the second insulating resin layer 40B of the second laminate 60B facing the second adhesive layer 20B of the adhesive layer 100, and performing hot pressing at, for example, a temperature exceeding the glass transition temperature of the resin constituting the first adhesive layer 20A and the second adhesive layer 20B of the adhesive layer 100.

[0165] [Example]

[0166] The present invention will now be specifically described through examples, but the present invention is not limited to these examples in any way. Furthermore, in the following examples, unless otherwise specified, various measurements and evaluations are based on the following content.

[0167] [Methods for determining amine value]

[0168] Weigh approximately 2g of the dimerized diamine composition into a 200mL–250mL Erlenmeyer flask. Using phenolphthalein as an indicator, add dropwise 0.1mol / L ethanolic potassium hydroxide solution until the solution turns light pink. Dissolve the solution in approximately 100mL of neutralized butanol. Add 3–7 drops of phenolphthalein solution and titrate with 0.1mol / L ethanolic potassium hydroxide solution while stirring until the sample solution turns light pink. Add 5 drops of bromophenol blue solution and titrate with 0.2mol / L hydrochloric acid / isopropanol solution while stirring until the sample solution turns yellow.

[0169] The amine value is calculated using the following formula (1).

[0170] Amine value = {(V2×C2)-(V1×C1)}×M KOH / m…(1)

[0171] Here, the amine value is expressed in mg-KOH / g, M KOH The molecular weight of potassium hydroxide is 56.1. Additionally, V and C represent the volume and concentration of the solution used in the titration, respectively. The subscripts 1 and 2 indicate a 0.1 mol / L ethanolic potassium hydroxide solution and a 0.2 mol / L hydrochloric acid / isopropanol solution, respectively. Furthermore, m is the sample weight in grams.

[0172] [Calculation of GPC and the percentage of area in the chromatogram]

[0173] (a) Dimeric diamine

[0174] (b) Monoamine compounds obtained by replacing the terminal carboxylic acid group of a monocarboxylic acid compound with a carbon number in the range of 10 to 40 with a primary aminomethyl or amino group.

[0175] (c) An amine compound obtained by replacing the terminal carboxylic acid group of a polybasic acid compound having a hydrocarbon group in the range of 41 to 80 carbon atoms with a primary aminomethyl or amino group (except for the dimer diamine).

[0176] Regarding GPC, a 100 mg solution was prepared by pretreating 20 mg of a dimerized diamine composition with 200 μL of acetic anhydride, 200 μL of pyridine, and 2 mL of tetrahydrofuran (THF). This solution was then diluted with 10 mL of THF (containing 1000 ppm cyclohexanone). The prepared sample was analyzed using a Tosoh (TOSOH) HLC-8220 GPC column at 50 μL injection volume and the following conditions: TSK-gel G2000HXL and G1000HXL columns. The flow rate was 1 mL / min, the column (oven) temperature was 40 °C, and the injection volume was 50 μL. Cyclohexanone was used as a standard to correct for elution time.

[0177] At this point, adjustments were made to change the retention time of the cyclohexanone peak from 27 minutes to 31 minutes, and to make the time from the start point to the end point of the cyclohexanone peak 2 minutes. Furthermore, the retention time of the main peak excluding the cyclohexanone peak was changed from 18 minutes to 19 minutes, and the time from the start point to the end point of the main peak excluding the cyclohexanone peak was changed from 2 minutes to 4 minutes and 30 seconds. Under these conditions, the following components (a) to (c) were then analyzed:

[0178] (a) The components represented by the main peak;

[0179] (b) The component represented by the GPC peak detected at a later time, based on the minimum value of the retention time later in the main peak;

[0180] (c) The component represented by the GPC peak detected at an earlier time, based on the minimum value of the retention time of the main peak at an earlier time.

[0181] [Determination of weight-average molecular weight (Mw)]

[0182] The weight-average molecular weight was determined using gel permeation chromatography (using an HLC-8220GPC manufactured by Tosoh Corporation). Polystyrene was used as the standard, and tetrahydrofuran (THF) was used as the developing solvent.

[0183] [Viscosity Measurement]

[0184] Viscosity at 25°C was measured using an E-type viscometer (Brookfield, trade name: DV-II+Pro). The rotation speed was set to a torque of 10% to 90%, and the viscosity was read after 2 minutes from the start of the measurement when it stabilized.

[0185] [Determination of Coefficient of Thermal Expansion (CTE)]

[0186] For a 3mm × 20mm polyimide film, a thermomechanical analyzer (Bruker 4000SA) was used to heat the film from 30°C to 265°C while applying a 5.0g load at a certain heating rate of 20°C / min. The film was then held at that temperature for 10 minutes and cooled at a rate of 5°C / min. The average coefficient of thermal expansion (CTE) from 250°C to 100°C was then calculated.

[0187] [Determination of relative permittivity (Dk) and dielectric loss tangent (Df)]

[0188] The relative permittivity and dielectric loss tangent of resin sheets (adhesive films, resin laminates) at 10 GHz were determined using a vector network analyzer (Agilent Technologies, trade name: E8363C) and an SPDR resonator. Furthermore, the materials used in the measurements were materials that had been placed at a temperature of 20°C–26°C and a humidity of 45%–55% RH for 24 hours.

[0189] [Determination of storage elastic modulus and glass transition temperature (Tg)]

[0190] The sample was cut into 5mm × 20mm pieces and heated in stages from 30°C to 400°C using a dynamic viscoelastic apparatus (DMA: UBM, trade name: E4000F) at a heating rate of 4°C / min, with measurements taken at a frequency of 11Hz. The maximum temperature at which the measured Tanδ value becomes the largest is defined as Tg.

[0191] [Determination of moisture absorption rate]

[0192] A sample (polyimide film or adhesive layer) of A4 size (transverse direction, TD: 210 mm × machine direction, MD: 297 mm) was dried in a hot air oven at 80°C for 1 hour, and its weight after drying was measured and recorded as the dry weight (W1). The sample after drying was then subjected to constant temperature and humidity (23°C, 50% RH) for 24 hours to absorb moisture, and its weight after moisture absorption was measured and recorded as the moisture absorption weight (W2). The moisture absorption rate was calculated by substituting the measured weights into the following formula.

[0193] Moisture absorption rate (wt%) = [(W2-W1) / W1] × 100

[0194] [Determination of Dimensional Change Rate]

[0195] Electrolytic copper foil (manufactured by Fukuda Metal Foil Powder Industry Co., Ltd., trade name: T49A-DS-HD2, thickness: 12μm) was overlapped on both sides of the adhesive layer. For adhesive films with a glass transition temperature of less than 160℃, hot pressing was performed for 40 minutes at 160℃ and 4MPa. For adhesive films with a glass transition temperature of 300℃ or higher, hot pressing was performed for 40 minutes at 390℃ and 4MPa. After obtaining the adhesive layer with copper foil, a test piece cut to 150mm square was used to expose and develop the dry film resist at 100mm intervals, thereby forming a target for position determination. After measuring the dimensions before etching (normal state) in an environment of 23±2℃ and 50±5% relative humidity, the copper outside the target material of the test piece was removed by etching (liquid temperature below 40℃, time within 10 minutes). After standing for 24±4 hours in an environment with a temperature of 23±2℃ and a relative humidity of 50±5%, the dimensions after etching were measured. The dimensional change rates relative to the normal state were calculated at three locations each in the MD direction (length direction) and TD direction (width direction), and the average value of each was taken as the dimensional change rate after etching. The dimensional change rate after etching was calculated using the following formula.

[0196] Dimensional change rate after etching (%) = [(BA) / A] × 100

[0197] A: Distance between targets before etching

[0198] B: Distance between etched targets

[0199] The codes used in this embodiment represent the following compounds.

[0200] PMDA: Pyromellitic dianhydride

[0201] BPDA: 3,3',4,4'-Biphenyltetracarboxylic acid dianhydride

[0202] BTDA: 3,3',4,4'-benzophenone tetracarboxylic dianhydride

[0203] m-TB: 2,2'-dimethyl-4,4'-diaminobiphenyl

[0204] TPE-R: 1,3-Bis(4-aminophenoxy)benzene

[0205] p-PDA: p-phenylenediamine

[0206] BAPP: 2,2-bis[4-(4-aminophenoxy)phenyl]propane

[0207] APB: 1,3-bis(3-aminophenoxy)benzene

[0208] NMP: N-methyl-2-pyrrolidone

[0209] DMAc: N,N-dimethylacetamide

[0210] DDA: An aliphatic diamine with 36 carbon atoms (distilled and purified from PRIAMINE 1074, manufactured by Croda Japan Co., Ltd., with an amine value of 210 mg KOH / g; a mixture of cyclic and chain-structured dimer diamines; component (a): 97.9%, component (b): 0.3%, component (c): 1.8%).

[0211] N-12: Dodecanedioic acid dihydrazide

[0212] OP935: Organic aluminum phosphinate (manufactured by Clariant Japan, trade name: Exolit OP935)

[0213] Furthermore, in the DDA, the "%" in components (a), (b), and (c) refers to the area percentage of the chromatogram in the GPC assay. Additionally, the molecular weight of the DDA is calculated using the following formula.

[0214] Molecular weight = 56.1 × 2 × 1000 / Amine value

[0215] (Synthesis example 1)

[0216] Under a nitrogen gas flow, 12.745 g of m-TB (0.0599 mol), 1.947 g of TPE-R (0.0066 mol), and DMAc with a post-polymerization solids concentration of 15 wt% were added to the reaction layer and stirred at room temperature to dissolve them. Then, 11.447 g of PMDA (0.0525 mol) and 3.86 g of BPDA (0.0131 mol) were added, and the polymerization reaction was continued for 3 hours at room temperature to prepare polyamic acid solution 1 (viscosity: 16,500 cps).

[0217] (Synthesis example 2)

[0218] Under a nitrogen atmosphere, 13.780 g of m-TB (0.0643 mol) and DMAc (with a post-polymerization solids concentration of 15 wt%) were added to the reaction layer and stirred at room temperature to dissolve them. Then, 6.903 g of PMDA (0.0317 mol) and 9.317 g of BPDA (0.0317 mol) were added, and the polymerization reaction was continued for 3 hours at room temperature to prepare polyamic acid solution 2 (viscosity: 12,500 cps).

[0219] (Synthesis example 3)

[0220] Under a nitrogen gas flow, 7.715 g of m-TB (0.0363 mol), 3.694 g of p-PDA (0.0363 mol), DMAc with a post-polymerization solid content of 15 wt%, 7.797 g of PMDA (0.0375 mol), and 10.524 g of BPDA (0.0375 mol) were added to the reaction layer, and the polymerization reaction was carried out by stirring at room temperature for 3 hours to prepare polyamic acid solution 3 (viscosity: 9,600 cps).

[0221] (Synthesis Example 4)

[0222] Under a nitrogen atmosphere, 9.061 g of p-PDA (0.0830 mol) and DMAc, with a post-polymerization solids concentration of 15 wt%, were added to the reaction layer and stirred at room temperature until dissolved. Then, 8.9112 g of PMDA (0.0409 mol) and 12.0275 g of BPDA (0.0409 mol) were added, and the polymerization reaction was continued for 3 hours at room temperature to prepare polyamic acid solution 4 (viscosity: 11,000 cps).

[0223] (Synthesis Example 5)

[0224] In a 500 mL four-necked flask equipped with a nitrogen inlet tube, stirrer, thermocouple, Dean-Stark trap, and cooling tube, 44.92 g of BTDA (0.139 mol), 75.08 g of DDA (0.141 mol), 168 g of NMP, and 112 g of xylene were added and mixed at 40 °C for 30 minutes to prepare a polyamic acid solution. The polyamic acid solution was heated to 190 °C and stirred for 4 hours to remove the distilled water and xylene from the system. Then, it was cooled to 100 °C, and 112 g of xylene was added and stirred. The mixture was then cooled to 30 °C to prepare an imidized polyimide solution 5 (solid content: 29.5 wt%, weight average molecular weight: 75,700).

[0225] (Synthesis Example 6)

[0226] In a 500 mL four-necked flask equipped with a nitrogen inlet tube, stirrer, thermocouple, Dean-Stark trap, and cooling tube, 47.67 g of BTDA (0.148 mol), 46.3969 g of DDA (0.085 mol), 16.601 g of APB (0.05679 mol), 155 g of NMP, and 103 g of xylene were added and mixed at 40 °C for 30 minutes to prepare a polyamic acid solution. The polyamic acid solution was heated to 190 °C and stirred for 4 hours to remove the distilled water and xylene from the system. Then, it was cooled to 100 °C, and 112 g of xylene was added and stirred. The mixture was then cooled to 30 °C to prepare imidized polyimide solution 6 (solid content: 29.5 wt%, weight average molecular weight: 85,200).

[0227] (Synthesis Example 7)

[0228] Under a nitrogen gas flow, 18.574 g of BAPP (0.0453 mol) and DMAc (15 wt%) and 9.7354 g of PMDA (0.0446 mol) were added to the reaction layer, and the polymerization reaction was carried out by stirring at room temperature for 3 hours to prepare polyamic acid solution 7 (viscosity: 5,300 cps).

[0229] (Production example 1)

[0230] Polyamic acid solution 1 was uniformly coated onto copper foil 1 (electrolytic copper foil, thickness: 12 μm, surface roughness Rz on the resin layer side: 0.6 μm) to a hardened thickness of approximately 50 μm, and then dried at 120 °C to remove the solvent. Then, a staged heat treatment from 120 °C to 360 °C was performed to complete imidization, preparing a single-sided metal-clad laminate 1. The copper foil 1 of the single-sided metal-clad laminate 1 was etched away using an aqueous ferric chloride solution to prepare a polyimide film 1 (thickness: 50 μm, CTE: 12 ppm / K, Dk: 3.3, Df: 0.0056, moisture absorption: 0.77 wt%, Tg: 378 °C).

[0231] (Production example 2)

[0232] Except for the use of polyamic acid solution 2, polyimide film 2 was prepared in the same manner as in Example 1 (thickness: 50 μm, CTE: 16.4 ppm / K, Dk: 3.4, Df: 0.0036, moisture absorption: 0.63 wt%, Tg: 332 °C).

[0233] (Production example 3)

[0234] Except for the use of polyamic acid solution 3, polyimide film 3 was prepared in the same manner as in Example 1 (thickness: 50 μm, CTE: 22.4 ppm / K, Dk: 3.6, Df: 0.0051, moisture absorption: 0.65 wt%).

[0235] (Production example 4)

[0236] Except for the use of polyamic acid solution 4, polyimide film 4 was prepared in the same manner as in Example 1 (thickness: 50 μm, CTE: 15.8 ppm / K, Dk: 3.8, Df: 0.0122, moisture absorption: 1.66 wt%, Tg > 400 °C).

[0237] (Production example 5)

[0238] Except that polyamic acid solution 2 was used and the cured thickness was approximately 25 μm, polyimide film 5 was prepared in the same manner as in Example 1 (thickness: 25 μm, CTE: 11.4 ppm / K, Dk: 3.4, Df: 0.0038, moisture absorption: 0.64 wt%).

[0239] (Production example 6)

[0240] 1.8 g of N-12 (0.0036 mol) and 12.5 g of OP935 were prepared by mixing 169.49 g (50 g of solids) of polyimide solution 5, and then diluting it with 6.485 g of NMP and 19.345 g of xylene to prepare polyimide varnish 1.

[0241] Polyimide varnish 1 was applied to the silicone-treated surface of a release substrate 1 (320mm x 240mm x 25μm) after drying to a thickness of 50μm. The varnish was then heated and dried at 80°C for 15 minutes and peeled off from the release substrate 1, thus preparing an adhesive film 1 (thickness: 50μm, CTE: 113ppm / K, Dk: 2.7, Df: 0.0024). Furthermore, the maximum values ​​of the storage elastic modulus of the adhesive film 1 after curing at 50°C and the maximum storage elastic modulus in the steep temperature gradient range of 180°C–260°C were 5.0 × 10⁻⁶. 2 MPa, 3.0MPa. In addition, the glass transition temperature of adhesive film 1 is 54℃.

[0242] (Production example 7)

[0243] 1.8 g of N-12 (0.0036 mol) and 12.5 g of OP935 were prepared by mixing 169.49 g (50 g of solids) of polyimide solution 6, and then diluting it with 6.485 g of NMP and 19.345 g of xylene to prepare polyimide varnish 2.

[0244] Except for the use of polyimide varnish 2, adhesive film 2 (thickness: 50 μm, CTE: 78 ppm / K, Dk: 2.7, Df: 0.0028) was prepared in the same manner as in Example 6. Furthermore, the maximum values ​​of the storage elastic modulus of adhesive film 2 after curing at 50°C and the maximum values ​​of the storage elastic modulus over the steep temperature gradient range of 180°C to 260°C were 15.0 × 10⁻⁶. 2 MPa, 12.0MPa. In addition, the glass transition temperature of adhesive film 2 is 120℃.

[0245] (Production example 8)

[0246] Polyamic acid solution 7 was uniformly coated onto copper foil 1 to a hardened thickness of approximately 50 μm, and then dried at 120°C to remove the solvent. Next, a phased heat treatment from 120°C to 360°C was performed to complete imidization, preparing a single-sided metal-clad laminate 2. The copper foil 1 of the single-sided metal-clad laminate 2 was etched away using a ferric chloride aqueous solution to prepare an adhesive film 3 (thickness: 50 μm, CTE: 58 ppm / K, Dk: 3.4, Df: 0.0059). Furthermore, the maximum values ​​of the storage elastic modulus of the adhesive film 3 after hardening at 50°C and the maximum storage elastic modulus in the steep gradient temperature range of 180°C–260°C were 29.0 × 10⁻⁶. 2 MPa, 21.0×10 2 MPa. In addition, the glass transition temperature of adhesive film 3 is 326℃.

[0247] (Production example 9)

[0248] Except that polyamic acid solution 2 was used and the cured thickness was approximately 12 μm, polyimide film 6 was prepared in the same manner as in Example 1 (thickness: 12 μm, CTE: 28.6 ppm / K, Dk: 3.4, Df: 0.0038, moisture absorption: 0.6 wt%).

[0249] [Example 1]

[0250] Polyimide varnish 1 was applied to the polyimide film 2 to a thickness of 25 μm after drying, and then heated and dried at 80°C for 15 minutes. Subsequently, polyimide varnish 1 was also applied to the opposite side to a thickness of 25 μm after drying, and then heated and dried at 80°C for 15 minutes to obtain adhesive layer 1. The evaluation results of adhesive layer 1 are shown in Table 1.

[0251] [Example 2]

[0252] Except that the dried thickness of polyimide varnish 1 was set to 50 μm, adhesive layer 2 was prepared in the same manner as in Example 1. The evaluation results of adhesive layer 2 are shown in Table 1.

[0253] [Example 3]

[0254] Except that polyimide film 5 was used instead of polyimide film 2, adhesive layer 3 was prepared in the same manner as in Example 2. The evaluation results of adhesive layer 3 are shown in Table 1.

[0255] [Example 4]

[0256] Except that polyimide film 1 was used instead of polyimide film 2, adhesive layer 4 was prepared in the same manner as in Example 2. The evaluation results of adhesive layer 4 are shown in Table 1.

[0257] [Example 5]

[0258] Except that polyimide film 3 is used instead of polyimide film 2, adhesive layer 5 is prepared in the same manner as in Example 2. The evaluation results of adhesive layer 5 are shown in Table 1.

[0259] Comparative Example 1

[0260] Except that polyimide film 4 is used instead of polyimide film 2, adhesive layer 6 is prepared in the same manner as in Example 2. The evaluation results of adhesive layer 6 are shown in Table 1.

[0261] [Example 6]

[0262] Except that polyimide varnish 2 was used instead of polyimide varnish 1, the adhesive layer 7 was prepared in the same manner as in Example 4. The evaluation results of the adhesive layer 7 are shown in Table 1.

[0263] Comparative Example 2

[0264] A polyamic acid solution 7 was uniformly coated onto the polyimide film 2 to a cured thickness of approximately 50 μm, and then dried at 120 °C to remove the solvent. Then, on the opposite side of the polyimide film 2, the same polyamic acid solution 7 was uniformly coated to a cured thickness of approximately 50 μm, and then dried at 120 °C to remove the solvent. Staged heat treatment from 120 °C to 360 °C was performed to complete imidization, resulting in an adhesive layer 8. The evaluation results of the adhesive layer 8 are shown in Table 1.

[0265] Comparative Example 3

[0266] Except that polyimide film 6 is used instead of polyimide film 2, adhesive layer 9 is prepared in the same manner as in Example 2. The evaluation results of adhesive layer 9 are shown in Table 1.

[0267] [Example 7]

[0268] Adhesive sheets (manufactured by Nikkan Industries, trade name: NIKAFLEX SAFY, thickness: 50 μm) were overlapped on both sides of the polyimide film 2 and hot-pressed for 40 minutes at a temperature of 160 °C and a pressure of 4 MPa to obtain adhesive layer 10. The evaluation results of adhesive layer 10 are shown in Table 1.

[0269] The results are summarized in Table 1.

[0270] [Table 1]

[0271]

[0272] As shown in Table 1, the adhesive layers of Examples 1 to 7 achieve both low dielectric loss tangent and dimensional stability. Therefore, when applied to circuit boards such as striplines that transmit high-frequency signals in the GHz band (e.g., 1 GHz to 50 GHz), transmission loss of high-frequency signals can be effectively reduced, and improved reliability and yield can be expected through excellent dimensional stability.

[0273] [Example 8]

[0274] A wiring substrate 1 is fabricated by forming multiple straight conductor patterns (circuit conductor width / space width = 100μm / 100μm) on the copper foil of a single-sided copper-clad laminate (manufactured by NIPPON STEEL Chemical & Material Co., Ltd., trade name: ESPANEX M series).

[0275] Prepare two wiring substrates 1. Apply an adhesive layer 2 to the circuit processing surface of the wiring substrate 1, and then place it on top of the other wiring substrate 1 with the circuit processing surface of the other wiring substrate 1 on the outside. Perform hot pressing for 40 minutes at a temperature of 160°C and a pressure of 4MPa to obtain a multilayer circuit substrate 1 {layer structure: wiring substrate 1 (circuit surface is the inside) / adhesive layer 2 / wiring substrate 1 (circuit surface is the outside)}.

[0276] [Example 9]

[0277] The two wiring substrates 1 are arranged with the circuit processing surfaces facing outwards, and then the two wiring substrates 1 are stacked by sandwiching an adhesive layer 2 between them. Otherwise, a multilayer circuit substrate 2 {stacked structure: wiring substrate 1 (circuit surface facing outwards) / adhesive layer 2 / wiring substrate 1 (circuit surface facing outwards)} is obtained in the same way as in Embodiment 8.

[0278] [Example 10]

[0279] On one side of a double-sided copper-clad laminate (manufactured by NIPPON STEEL Chemical & Material Co., Ltd., trade name: ESPANEX M series), multiple straight conductor patterns (circuit conductor width / space width = 100μm / 100μm) are formed by etching using a subtractive method to create wiring substrate 2.

[0280] An adhesive layer 2 is disposed on the circuit processing surface of the wiring substrate 2, and then disposed thereon with the copper foil side of the single-sided copper clad laminate facing outwards. Otherwise, a multilayer circuit substrate 3 {layer structure: wiring substrate 2 (copper foil side facing outwards, circuit surface facing inwards) / adhesive layer 2 / single-sided copper clad laminate (copper foil side facing outwards)} is obtained in the same manner as in Embodiment 8.

[0281] [Example 11]

[0282] Multiple straight conductor patterns (circuit conductor width / space width = 100μm / 100μm) are formed on the copper foils on both sides of the double copper-clad laminate by etching using the subtractive method, thus creating wiring substrate 3.

[0283] Except that wiring substrate 3 is used instead of wiring substrate 2, a multilayer circuit substrate 4 {layer structure: wiring substrate 3 / adhesive layer 2 / single-sided copper clad laminate (copper foil side is the outside)} is obtained in the same way as in Example 10.

[0284] [Example 12]

[0285] Except that a wiring substrate 1 is used instead of a single-sided copper-clad laminate and the wiring substrate 1 is configured with the circuit processing surface of the wiring substrate 1 as the outside, a multilayer circuit substrate 5 {layer structure: wiring substrate 2 (copper foil surface as the outside, circuit surface as the inside) / adhesive layer 2 / wiring substrate 1 (circuit surface as the outside)} is obtained in the same way as in embodiment 10.

[0286] [Example 13]

[0287] Except that wiring substrate 3 is used instead of wiring substrate 2, a multilayer circuit substrate 6 {layer structure: wiring substrate 3 / adhesive layer 2 / wiring substrate 1 (circuit surface is the outside)} is obtained in the same way as in embodiment 12.

[0288] [Example 14]

[0289] Prepare two single-sided copper-clad laminates, two adhesive layers 2, and a wiring substrate 1. Stack them in a structure of single-sided copper-clad laminate (copper foil side is the outside) / adhesive layer 2 / wiring substrate 1 (circuit side orientation is not specified) / adhesive layer 2 / single-sided copper-clad laminate (copper foil side is the outside). Perform hot pressing for 40 minutes at a temperature of 160°C and a pressure of 4MPa to obtain a multilayer circuit board 7.

[0290] The embodiments of the present invention have been described in detail above for illustrative purposes, but the present invention is not limited to the described embodiments and can be modified in various ways.

Claims

1. An adhesive layer, comprising: The resin composition is a non-thermoplastic polyimide layer of non-thermoplastic polyimide; The first adhesive layer is laminated on one side of the non-thermoplastic polyimide layer; as well as The second adhesive layer is laminated on the opposite side of the non-thermoplastic polyimide layer to the first adhesive layer. The adhesive layer is characterized by satisfying the following conditions a to c: a) The overall thickness of the adhesive layer is in the range of 100 μm or more and 300 μm or less, and the ratio of the thickness of the non-thermoplastic polyimide layer to the overall thickness of the adhesive layer is in the range of 0.3 or more and 0.9 or less. b) The moisture absorption rate measured after drying at 80°C for 1 hour and conditioning at 23°C and 50%RH for 24 hours is less than 0.4% by weight. c) The storage elastic modulus of the first adhesive layer and the second adhesive layer at 50°C is independently below 1800 MPa, and the maximum value of the storage elastic modulus at 180°C to 260°C is independently below 800 MPa.

2. The adhesive layer according to claim 1 further satisfies the following condition d: d) After conditioning for 24 hours under constant temperature and humidity conditions of 23℃ and 50%RH, the dielectric loss tangent at 10 GHz, measured using a split-column dielectric resonator, was below 0.

004.

3. The adhesive layer according to claim 1 or 2, wherein, The glass transition temperatures (Tg) of the first adhesive layer and the second adhesive layer are both below 180°C.

4. The adhesive layer according to claim 1 or 2, wherein, Both the first adhesive layer and the second adhesive layer contain polyimide as a resin component. The polyimide contains anhydride residues derived from the tetracarboxylic anhydride component and diamine residues derived from the diamine component, and contains more than 50 mol% of diamine residues derived from the dimer diamine composition, wherein the dimer diamine composition is a dimer diamine whose main component is a dimer diamine formed by replacing the two terminal carboxylic acid groups of the dimer acid with primary aminomethyl or amino groups.

5. The adhesive layer according to claim 1 or 2, wherein, The coefficient of thermal expansion of the non-thermoplastic polyimide layer is in the range of 1 ppm / K or higher and 30 ppm / K or lower.

6. The adhesive layer according to claim 1 or 2, wherein, After being conditioned for 24 hours under constant temperature and humidity conditions of 23°C and 50%RH, the dielectric loss tangent of the non-thermoplastic polyimide layer at 10 GHz, as measured by a split column dielectric resonator (SPDR), was below 0.

006.

7. The adhesive layer according to claim 1 or 2, characterized in that, The polyimide constituting the non-thermoplastic polyimide layer comprises tetracarboxylic acid residues and diamine residues, wherein the content of diamine residues derived from the diamine compound represented by the following general formula (A1) is 50 mol% or more relative to all diamine residues. In formula (A1), the linker Z represents a single bond or -COO-, Y independently represents a monovalent hydrocarbon with 1 to 3 carbon atoms that can be substituted by a halogen atom or a phenyl group, or an alkoxy group with 1 to 3 carbon atoms, or a perfluoroalkyl group or alkenyl group with 1 to 3 carbon atoms, n represents an integer from 0 to 2, and p and q independently represent integers from 0 to 4.

8. A circuit board comprising an adhesive layer as described in any one of claims 1 to 7.

9. A strip line, comprising: First metal layer; The first insulating resin layer comprises one or more layers stacked on one side of the first metal layer; The wiring layer is grounded to the first insulating resin layer; Second metal layer; The second insulating resin layer comprises one or more layers laminated on one side of the second metal layer; and An intermediate resin layer exists between the first insulating resin layer and the second insulating resin layer in a stacked configuration. The intermediate resin layer includes an adhesive layer as described in any one of claims 1 to 7, and the wiring layer is covered by the first adhesive layer or the second adhesive layer.

Citation Information

Patent Citations

  • Metal-clad laminate sheet and circuit board

    JP2018170417A

  • Metal-clad laminate and circuit board

    JP2020055186A

  • Resin film, coverlay film, circuit board, copper foil with resin, metal-clad laminate, multilayer circuit board, polyimide and adhesive resin composition

    JP2020056011A